Bangana brevirostris, a new species of cyprinid fish (Teleostei: Cypriniformes) from the Lancang-Jiang (Upper Mekong River) drainage in Yunnan, Southwest China - Liu, Kai; Zhou, Wei (Zootaxa, 2009)
Bangana brevirostris, new species, is described from the Lancang-Jiang in Yunnan, Southwest China. It can be distinguished from all other congeners by the following combination of characters: a pair of minute rostral barbels; mental groove short and shallow; dorsal fin with 12–13 branched rays; 42–44 lateral line scales; eye large, its diameter 28.1–32.9 % of head length; snout short, its length 25.5–32.7 % of head length. It shares the same postlabial groove-type with Bangana dero and B. devdevi, which makes them very different from other congeners.